Exploring therapeutic responsiveness: a comparative textual analysis across different models - Davì, Dario; Prestano, Claudia; Vegni, Nicoletta (Frontiers in Psychology, 2024)
The purpose of this study is to examine therapeutic responsiveness across three different therapeutic models. The construct of responsiveness consists of two conceptual features: optimal responsiveness, which involves adapting therapist behavior to the unique therapeutic relationship, and appropriate responsiveness, a more refined concept. While aligned with interpersonal principles, the responsiveness construct challenges prevailing statistical methods by emphasizing the therapist's adaptive responses. A comparative analysis of Gestalt, psychodynamic, and systemic therapies revealed unique patterns of responsiveness within each model, ranging from an emphasis on empathy and intuition to the significance of countertransference. Methodologically, a literature review and textual analysis using Atlas.ti allowed for nuanced exploration. The results also revealed a core commonality—"experience"—across these models, positioning responsiveness as an "extra-specific" factor amidst shared conceptual ground. In conclusion, this study sheds light on the nuances of responsiveness, which is central to advancing psychotherapeutic practice in an evolving landscape. An in-depth examination of the construct of responsiveness helps identify therapist characteristics that can be enhanced, enriched, and supported during training and supervision.